Mother–child conversations and coping strategies as antecedents of children’s recall accuracy - Lee, Seungjin; Kim, Juyoung (Frontiers in Psychology, 2025)
IntroductionConsidering that the level of stress during a distressing event can decrease children’s abilities to encode and store event-related information, and thereby their recall accuracy of the event, it is imperative to identify factors that can reduce the risk of high stress. This study explored cascading relations from mother–child conversations to children’s strategies for coping with stress to their recall accuracy regarding dental treatment to examine antecedents of recall accuracy related to a distressing event.MethodsEighty 5- to 10-year-old children (41 boys, 39 girls) and their mothers participated in the study. Mother–child conversations and children’s coping strategies were, respectively, measured via coding based on mothers’ reports and children’s self-reports. Recall accuracy was assessed using the proportion of accurate free-recall reports and suggestibility in a memory interview.Results and discussionEmotion-oriented conversations predicted higher recall accuracy (including more accurate free recall and less suggestibility) directly and indirectly through more use of positive coping strategies and less use of negative coping strategies. These results suggest that it is critical to consider the complex impacts of individual differences when studying children’s recall accuracy regarding stressful past events, especially in terms of interviewing child witnesses.